Well Decommission, Policy, Processes, and the Urban Environment. (December 2016) - Hodder, Eric A.
Abstract: An afterthought in many well construction and design plans is the regulatory compliant destruction or decommission of the well at some point in the future. Agricultural lands that evolved into urban areas in southern California are likely to have thousands of lost or unmanaged wells. For the general public, landowners, and others these wells pose safety, environmental, logistical, and monetary issues. This discussion will cover regulatory guidelines, procedures, and case examples of well decommissioning. In California, regulations for well destruction are rooted in Department of Water Resources bulletins, state water code, legislation, local ordinance, and drilling contractor licensing compliance. In most cases the county departments of public health take the lead role for permitting and enforcing well destruction requirements. Well terminology used can be misleading; for example, by state law, an abandoned well is a noncompliant hazard‐ not a safely destroyed or decommissioned well adhering to standards. Permitted well decommission typically involves cement‐bentonite sealing and casing perforation. With the goal of effective prevention of surface liquid intrusion or aquifer cross contamination, sometimes explosives, over‐drilling, and other practices are applied. Challenges are frequent in locating and decommissioning abandoned wells. Lost records lead to reconnaissance, geophysical investigations, and excavation of unintended anomalies. Urban development may surround an abandoned well within a structure, foundation, or utilities. Environmentally sensitive areas will affect standard techniques. With increasing water demand and urbanization, effective well decommission is important for analysis and regulatory emphasis.